Adult day care provision in Kuching, Sarawak : Positive aging or social isolation? - Kaur, Parveen; Au, Yong Seh Jin; Lim, Wei Chi; Zoferi, Nurul ‘Ain Natasya; Jawaid, Arif (Universiti Malaysia Sarawak (UNIMAS), 2017)
Ageing is a barrier for old people to fully engage in social activities. The population of senior citizens is growing at a fast pace globally. Therefore, certain organizations have been making effort to ensure that they stay happily and contribute to society, thus reducing social problems. One of the services organized is adult day care services. Due to the modern medical technology and professional health care system, the longevity of a person has advanced. The purpose of this research is to investigate the role of adult day care services in this modern era. The samples of this research were eight senior citizens and ten care workers. This research was carried out in five branches of Kenneth Care home which are located in Kuching, Sarawak. This study used qualitative method to get more information and detail answers from the respondents. Indepth interview using questionnaires and systematic observation were utilised in this research. Findings of this study show that the use of adult day care in Kuching is not attractive and conducive to the respondents. Moreover, the majority of the respondents showed great concerns about the provision of services. This study would benefit the care-workers, the senior citizens, and their stakeholders. Subsequently, it will help to improve the provision provided.